Surgical Resolution of Bilateral Hypertrophy of Masseter Muscle Through Intraoral Approach - Dos Santos Trento, Guilherme [UNESP]; Benato, Leonardo Silva; Rebellato, Nelson Luis Barbosa; Klüppel, Leandro Eduardo (Wolters Kluwer, 2017)
Masseter muscle hypertrophy is an untypical anomaly with no definite cause and its diagnosis is easily completed through physical examination and imaging examinations. In some cases, patient may report signs and symptoms of well-localizated pain. However, it is generally asymptomatic and patient's chief complaint is about esthetic because of facial asymmetry. In this case, surgery is carefully indicated. The aim of this article is to report a case of a male patient with no painful and functional complaints but an important unease over his facial asymmetry. Patient underwent surgery involving bilateral resection of mandibular angles and unilateral resection of masseter muscle through intraoral approach. Surgical approaches and techniques rely heavily on surgeon. There are few reports in the literature about this anomaly, but those available present several techniques. The surgeon's dexterity and knowledge become extremely important, whereas this procedure is essentiallyesthetic.
Keywords: Esthetics; facial asymmetry; hypertrophy; masseter muscle; surgery